Efficacy of ultrasound cyclo-plasty in patients with refractory glaucoma - Hui-Min Zhong; Xiao-Hong Liu; Shou-Yue Huang; Hui-Ping Yao; Yi-Sheng Zhong; Jing Wang (International Journal of Ophthalmology)
AIM: To assess the efficacy and safety of ultrasound cyclo-plasty (UCP) in lowering intraocular pressure (IOP) among Chinese patients suffering from refractory glaucoma. METHODS: In this 12-month retrospective study, 28 patients with refractory glaucoma (IOP≥25 mm Hg) were treated with 8-second UCP using either 8 or 10 probe sectors. The principal measure of efficacy was the decrease in IOP at the following intervals after UCP: 1d, 1, 3, 6, and 12mo, with each measurement compared to baseline. RESULTS: Mean IOP (in mm Hg) was reduced from 46.8±8.9 to 24.5±3.2, 27.0±4.8, 29.1±4.6, 26.1±4.5, and 28.3±4.8 at 1d, 1, 3, 6, and 12mo postoperatively, respectively. Compared to baseline, IOP reductions at these time points were 45.0%, 39.9%, 35.3%, 41.4%, and 36.7%, respectively. Most patients experienced relief from ocular pain after surgery. No cases of choroidal detachment or hypotony was observed. CONCLUSION: UCP is effective in reducing IOP among Chinese patients with refractory glaucoma and shows a favorable safety profile.